Conflict Mapping of Gunung Ciremai National Park in Cisantana Village, Cigugur, Kuningan, West Java - Maria , Maria Palmolina; Eva, Eva Fauziyah (Forestry Department, University of Muhammadiyah Makassar, 2020)
The purpose of this study is to conflict mapping, explain conflict style of stakeholder and choices of conflict resolution. This study was conducted in February 2017 in Cisantana Village, Kuningan Regency. Data were collected through participatory rural appraisal; interviews, field observation, documentation and focus group discussions. The study method was used Rapid Land Tenure Assessment (RaTA) and Dispute Style Analysis (AGATA). The results showed that the dominant conflict in TNGC was the change of forest status which affected the economic activities of the community around TNGC, that involved eight dominant actor. In a conflict, the stakeholder has a different style of dispute. The stakeholders was facilitated and mediated to propose a permit to manage Patulungan (parking management), and a permit to manage Ipukan (tourism guide). In this case, the role of outsiders who do not have a conflict relationship is needed in order to realize conflict resolution.